Manajemen dan Mitigasi Risiko Lender Peer-To-Peer Lending Pasca Diundangkan POJK 10/2022 - Shalmont, Jerry; Darmawan, Grace Iskandar; Dominica, Dora (UI Scholars Hub, 2023)
Peer to Peer Lending (P2P Lending) has become one of the financing options for both individuals and businesses. The use of P2P Lending during the COVID-19 pandemic has significantly increased from both borrowers and lenders. Recently, the issue of P2P Lending that is often discussed pertains to borrowers, but the lenders seem to be forgotten and not receiving special attention, even though lenders also require protection because they can at least protect themselves from the unwanted risk of default. This research is relevant because it is expected to provide information related to the management of P2P Lending companies and how to mitigate risks as a P2P Lending lender. The research results indicate that when investing, it's essential to consider not only the legality but also commercial aspects such as ease of fund transfer and withdrawal, collateral, and the 90-day past due rate. The approach to be used is a legal and conceptual approach.